Broadband Compact MIMO Antenna Employing CRLH Transmission Lines with High Isolation - Liangyuan Liu; Xiangqun Shi (International Journal of Antennas and Propagation)
A broadband and planar multiple-input multiple-output (MIMO) antenna with pattern diversity is presented in this letter. The four-port MIMO antenna is designed by using a novel metamaterial structure with small dimensions of 60 × 60 × 1.6 mm3. Each radiating element of the MIMO antenna is comprised of composite right/left-hand (CRLH) transmission lines (TLs). Between its four elements, there are four open L-shaped slot loading on the ground plane of the patch antenna system. The antenna obtains the wide frequency range of 2.31–4.99 GHz. In addition, The proposed antenna has an isolation greater than 20 dB between its four elements. The MIMO antenna has excellent bandwidth performance and good diversity properties between elements.